النظام التأديبي للموظف العام في التشريع الجزائري - بوسعد حنان - وضاح عبلة (المسيلة, 2023)
Disciplining a public official for professional errors is one of the means by which employees' actions are controlled Any error by the staff member subjects the staff member to disciplinary punishment and the department that has the power to appoint imposes the penalty, However, granting it broad discretion to consider or not consider positive or negative acts as professional errors punishment ", is the result of non-identification of professional errors exclusively contrary to disciplinary sanctions received exclusively specified. Since the disciplinary administrative authority has a dual role both when acting as an adversary by identifying elements of error and when exercising a role of sentencing. The legislator gave the employee a number of safeguards necessary to achieve the fairness of the disciplinary penalty and to provide reassurance to the same official, particularly the judicial guarantee that enabled the administrative judge to exercise full judicial control over disciplinary decisions. Keywords: disciplinary system, public official, Algerian legislation, errors, penalties.
Keywords: المو ظف العام - النظام التاديبي - القانون الاداري -الاخطاء - العقوبات